MEMBANGUN MUSLIM ENTREPRENEURSHIP: DARI PENDEKATAN KONVENSIONAL KE PENDEKATAN SYARIAH - Ita Nurcholifah (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
Currently there are so many problems that this nation faces. Muslims as a part of thenation must take part in recovering economic condition.Therefore,Muslims especially those youngstersshould be galvanized to become great entrepreneur.The spirit of Muslimsentrepreneurship can be established through education at home, surroundings, and school. There are several strategies to internalize entrepreneurship spirit for Muslims: first, their confidence should be boosted.Second, their motivation to work hard must be enhanced. Third, they should be taught to become open-minded persons so that they are able control themselves. Fourth, they should be trained to be dependable or istiqāmah. Fifth, they should be trained to be accurate and precise. Sixth, their creative thinking should be improved. Seventh, they should be trained to solve complicated and various problems. Eighth, they should be trained to be objective in judging something.